The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1002/jmri.25166
|View full text |Cite
|
Sign up to set email alerts
|

Computational postprocessing quantification of small bowel motility using magnetic resonance images in clinical practice: An initial experience

Abstract: Motility quantitation revealed a significant difference in motility of terminal ileum in patients with small bowel CD compared with healthy subjects, concording with visible dysmotility and inflammatory changes. J. Magn. Reson. Imaging 2016;44:277-287.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 40 publications
2
26
1
Order By: Relevance
“…MRI is non‐invasive, safe and widely available and, coupled with advances in post‐processing technologies, enables rapid and repeatable quantification . Encouragingly, the first steps toward clinical implementation have been taken with dynamic motility imaging now being routine in various centers and with several prospective clinical studies being published …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…MRI is non‐invasive, safe and widely available and, coupled with advances in post‐processing technologies, enables rapid and repeatable quantification . Encouragingly, the first steps toward clinical implementation have been taken with dynamic motility imaging now being routine in various centers and with several prospective clinical studies being published …”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7][8][9][10][11] Encouragingly, the first steps toward clinical implementation have been taken with dynamic motility imaging now being routine in various centers and with several prospective clinical studies being published. [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] The gastrointestinal tract is complex, undergoing fasted and fed contractile cycles that take place over hours, such as the migrating motor complex. 20 It is not practical to perform prolonged MRI imaging of the intestine in a clinical setting.…”
mentioning
confidence: 99%
“…20,26,31,42,48 The motility in the terminal ileum was lower in Crohn's patients in comparison to healthy subjects. 42 It has been shown that the lesion detection rate is increased when static and dynamic MRI is combined. 25,49 The motility patterns in Crohn's disease revealed reduced contraction-wave frequencies, amplitudes, and decreased luminal occlusion rates.…”
Section: Crohn's Diseasementioning
confidence: 95%
“…Several studies show that small bowel motility quantified with dynamic MRI can be used as a biomarker of inflammatory activity in Crohn's disease and to differentiate healthy from diseased bowel . The motility in the terminal ileum was lower in Crohn's patients in comparison to healthy subjects . It has been shown that the lesion detection rate is increased when static and dynamic MRI is combined .…”
Section: Clinical Implementationmentioning
confidence: 99%
See 1 more Smart Citation